Replacement names for botanical taxa involving algal genera - Blanco, Saúl; Wetzel, Carlos E. (Phytotaxa, 2016)
A cross-check of botanical names databases revealed the presence of 19 cases of homonymy which are hereby resolved by proposing replacement names. Most cases concern diatom genera (Bacillariophyta) names which are preoccupied by spermatophytes. While Loranthella nom. nov. (Spermatophyta, Loranthaceae) and Ochradiscus nom. nov. (Spermatophyta, Resedaceae) are proposed as new names for spermatophytes, new diatom names are proposed for genera that are currently placed in the families Amphipleuraceae, Coscinodiscaceae, Hemiaulaceae, Hemidiscaceae, Melosiraceae, Metascolioneidaceae nom. nov., Naviculaceae, Pyxillaceae, Stictodiscaceae and Surirellaceae. With one exception (i.e. Eileencoxia nom. nov.) all remaining diatom genera that are discussed in the present paper are marine and/or fossil elements. The particularities of each case are briefly discussed. A total of one hundred and three new combinations are proposed.